epsilon-Aminocaproic acid esters as transdermal penetration enhancing agents - Dolezal, P; Hrabálek, A; Semecký, V (Pharmaceutical research, 1993)
The synthesis of epsilon-aminocaproic acid esters is described. Two representative members from a group of five of the 1-alkyl homologues synthetized as flexible analogues of 1-alkylazacyclohepatanone derivatives were evaluated in vitro for their effectiveness on the transport of theophylline through the excised human cadaver skin in comparison with Azone. The 1-octyl- and 1-dodecyl-epsilon-aminocaproic acid esters (OCEAC and DDEAC) show excellent penetration enhancement. Donor samples contained 2.5% theophylline and 1% enhancers tested in three different vehicles. Fluxes of theophylline were increased with OCEAC about 19 times from olive oil, 45 times from water, and about 38 times from water-propylene glycol (3:2) vehicle toward controls (with DDEAC about 17, 39, and 35 times, respectively) and they were markedly higher than Azone under the given conditions. Acute LD50's (i.p. in mice) of OCEAC (DDEAC) were 245 mg/kg (352 mg/kg), with a slightly lower toxicity than Azone. OCEAC and DDEAC did not exhibit acute dermal irritation in vivo on rabbits at a 5% concentration in white petrolatum.
Keywords: myši; mužské pohlaví; aminokapronáty; Male; Administration, Cutaneous; Indicators and Reagents; theofylin; rozpustnost; Female; Humans; Irritants; Azepines; lidé; činčila; králíci; ženské pohlaví; dráždivé látky; chemická stimulace; aplikace kožní; techniky in vitro; Aminocaproic Acid; Theophylline; indikátory a reagencie; azepiny; LD50; Animals; Lethal Dose 50; Mice; zvířata; kyselina 6-aminokapronová; In Vitro Techniques; Solubility; Aminocaproates; Rabbits; Stimulation, Chemical; Skin Absorption; Chinchilla; kožní absorpce